Emotional Intelligence and Parents Attachment to Adjustment among First-Year Students at Dayah - Liza, Suci Zahratul; Zulkarnain, Zulkarnain; Yurliani, Rahma (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2024)
Life at dayah has rules and routine activities that the students must follow. This situation can cause pressure if the students are unable to adapt. The success of students in adapting is also influenced by several factors, including emotional intelligence and parental attachment. This research aims to determine: 1) the influence of emotional intelligence to adjustment; 2) the influence of parents attachment to adjustment; and 3) the influence of emotional intelligence and parents attachment to adjustment among first-year students at dayah. The sample in this study was 200 students from class VII, with the sampling technique being total sampling. The measurement tools used are adjustment scale, emotional intelligence scale, and parents attachment scale. The results of the research show that: 1) emotional intelligence positively and significantly influenced to adjustment p= .000, r= .593); 2) parents attachment positively and significantly influenced to adjustment (p= .030, r= .154); and 3) emotional intelligence and parents attachment influenced to adjustment among first-year students at dayah (p= .000, r= .595). The implication of this research is to develop emotional intelligence and parents attachment to improves better adjustment.